The left DTI-ALPS index: a potential glymphatic mediator of cognitive and motor dysfunction in Parkinson’s disease - Li, Yanyan; Song, Jian; Zhao, Yuqing; Lin, Zengru; Pan, Xingduo; Li, Ming; Zhou, Xiaoyan; Zhang, Zhen; Wei, Wei; Xue, Xiehua (Frontiers in Medicine, 2025)
IntroductionThis study employed the Diffusion Tensor Imaging Along the Perivascular Space (DTI-ALPS) index to evaluate glymphatic function in patients with Parkinson’s disease (PD) and investigated its association with cognitive and motor functions.MethodsClinical data from the PD group (n = 64) and the healthy control group (HC, n = 30), matched for age, sex, and education years, were included. Based on Montreal Cognitive Assessment (MoCA) scale, PD patients were further categorized into subgroups. All participants underwent DTI scan and scale assessments.ResultsCompared with the HC group, the PD group exhibited increased diffusivity of both the left projection (Dzzproj) and association fibers (Dzzassoc) along the z-axis (p < 0.05) and a reduced left DTI-ALPS index (p < 0.05). The left Dzzproj was negatively correlated with MoCA score (r = −0.299, p = 0.024, q = 0.048). The left Dzzassoc was negatively correlated with MoCA score (r = −0.280, p = 0.035, q = 0.035), and Movement Disorder Society-Unified Parkinson’s Disease Rating Scale III (MDS-UPDRS III) score (r = 0.333, p = 0.011, q = 0.022). The left DTI-ALPS index showed positive correlations with MoCA score (r = 0.350, p = 0.008, q = 0.015) and a negative correlation with MDS-UPDRS III score (r = −0.322, p = 0.015, q = 0.015). Within the PD subgroup analysis, when compared to the HC group, and throughout the progression from PD with cognition normal (PDCN) to PD with dementia (PDD), left Dzzproj (F = 10.240, P < 0.001), and left Dzzassoc (F = 11.060, p < 0.001) all demonstrated a stepwise increasing trend. Conversely, the MoCA total score (F = 259.985, P < 0.001) and the left DTI-ALPS index (F = 11.060, P < 0.001) exhibited a stepwise decreasing trend. Mediation analysis revealed that the left DTI-ALPS index mediated the effect of MoCA scores on MDS-UPDRS III scores.ConclusionAbnormalities in the left DTI-ALPS index and diffusivity reflect underlying glymphatic system (GS) dysfunction and white matter microstructural damage in PD patients. These neuropathological changes are significantly associated with, and collectively contribute to, the progression of motor and cognitive decline. Furthermore, the left DTI-ALPS index shows promise as a novel biomarker for identifying cognitive impairment in PD patients.